Valoración económica ambiental de la laguna de Pias (Pataz) - La Libertad - Perú - Ugarte Lopez, Wilmer (2019)
ABSTRACT In this research work, the main environmental services and the environmental economic valuation of the Pías lagoon are determined, in the district of Pías, Province of Pataz, department of La Libertad. The Laguna de Pías has been formed by a natural embalming of the river, which is born from the union of several ravines over 4100 m.a.s.l. and that reach the lagoon. Waters below the lagoon, the river continues its course until joining the Marañón river by its right bank. For the present investigation the Contingent Valuation Method (MVC) was used, where users of the environmental services of the lagoon are asked and their willingness to pay to conserve said environmental good, through surveys or interviews as a Environmental economic assessment instrument, the Fisher-Arkin-Colton table was used to calculate the sample size. It was applied in 84 surveys to residents of the area and visitors. The results indicate that the main services we have: scenic beauty, fishing, tourism and recreation, photographic photography, navigation, as well as water regulation, sediment control, chemical water quality, climate regulation, nutrient recycling, atmospheric carbon capture , shelter for water birds, sediment retention, etc. The economic value of the willingness to pay (DAP) for conserving the aquatic environment with respect to the environmental service provided by the Pías lagoon, which ranged from consumer surplus (Ec) 3215.85 Nuevos Soles, the integral result with its individual form (ECI) 38,284 Nuevos Soles, and finally the annual value that is approximately 63 436,588 nuevos soles.